Paucicellular infiltrating ductal carcinoma of pancreas: an unusual variant. - Fagih, M; Serra, S; Chetty, R (2007)
A 65-year-old man presented with obstructive jaundice from a 3-cm mass in the head of the pancreas. A Whipple resection was performed. Histologic examination of the tumor showed scanty tumor cells arranged in a single-file manner set within a desmoplastic sclerotic stroma. In other areas, the tumor was arranged around preexisting ducts in a targetoid fashion. Very focal ductal and signet-ring cell differentiation was noted. This unusual variant of pancreatic cancer was characterized by paucicellularity and a pattern of invasion resembling lobular carcinoma of breast.